2022
DOI: 10.1021/acsnano.2c08013
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenic Cell Death Augmented by Manganese Zinc Sulfide Nanoparticles for Metastatic Melanoma Immunotherapy

Abstract: Both T-cell deprivation and insufficient tumor immunogenicity seriously hinder the efficacy of immunemediated tumor destruction in melanoma. In this work, an amphiphilic polyethylene glycol-poly(2-hexoxy-2-oxo-1,3,2-dioxaphospholane) copolymer with a thermally sensitive flowable core (mPEG-b-PHEP) was chosen to incorporate IR780 dye and manganese zinc sulfide nanoparticles (ZMS) to form polymer micelles (denoted PP IR780-ZMS ), which precisely controlled the release of ZMS after being triggered by nearinfrared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(73 citation statements)
references
References 64 publications
1
72
0
Order By: Relevance
“…MnO@curcumin@IR780 nanoparticles exhibited a broad absorption band (∼600–800 nm) and an obvious PL peak at ∼780 nm, which was attributed to IR780, demonstrating the successful decoration of IR780 on the MnO@curcumin nanoparticles. In comparison to IR780, the broadening absorption bands and shifting emission peaks of MnO@curcumin@IR780 nanoparticles might be attributed to the hydrophobic interaction and the changes in solvent polarity, as well as molecular interactions between IR780 and MnO@curcumin nanoparticles, a finding well consistent with previous reports. , The increased hydrodynamic size, altered absorption/PL spectra, and color change of the samples suggested that MnO (MnO@curcumin) nanoparticles were successfully functionalized with curcumin (IR780).…”
Section: Resultssupporting
confidence: 89%
“…MnO@curcumin@IR780 nanoparticles exhibited a broad absorption band (∼600–800 nm) and an obvious PL peak at ∼780 nm, which was attributed to IR780, demonstrating the successful decoration of IR780 on the MnO@curcumin nanoparticles. In comparison to IR780, the broadening absorption bands and shifting emission peaks of MnO@curcumin@IR780 nanoparticles might be attributed to the hydrophobic interaction and the changes in solvent polarity, as well as molecular interactions between IR780 and MnO@curcumin nanoparticles, a finding well consistent with previous reports. , The increased hydrodynamic size, altered absorption/PL spectra, and color change of the samples suggested that MnO (MnO@curcumin) nanoparticles were successfully functionalized with curcumin (IR780).…”
Section: Resultssupporting
confidence: 89%
“…All staining was conducted according to the corresponding standard experimental protocols. 48 All images of tissue slides were acquired by the Tissue FAXS Plus S system (TissueGnostics GmbH, Austria).…”
Section: Cotherapy With Zrc-pvp Nds In Vivomentioning
confidence: 99%
“…The polymeric system is introduced along with the addition of IR-775 dye for better uptake and entrapment of polyphenols into the hydrophobic cores, resulting in a self-assembled nano-carrier system for profound drug delivery . Some studies have shown that the uptake of hydrophobic moieties in the polymeric nanosystem participates in structural, metabolic, and signaling pathways that target cancer cells, promoting cell death through up-/down-regulation of signaling pathways. , The presence of hydrophobic fluorescent IR-775 dye in the nanosystem enhances the uptake of active polyphenol molecules to achieve maximum yield when encapsulated with PLA . Herein, we report that P p IR NPs can serve as multifunctional nanosystems for bioimaging and be used for commingled PDT/PTT upon validation.…”
Section: Introductionmentioning
confidence: 99%